Measurement of the Equality of the Drug Welfare Induction Level of Chinese Patients With Chronic Diseases in Gansu, Sichuan, Hebei, and Zhejiang Based on the Bivariate Theil-T Index Method - Tang, Shaoliang; Zhang, Ruxia; Si, Yinghang; Cheng, Yan; Gong, Ying (Frontiers in Public Health, 2020)
Objectives: This study aimed to measure the induction level of drug welfare in Chinese patients with chronic diseases using a bivariate Theil index. Design: The bivariate Theil-T index was used to hierarchically decompose the relevant survey data, and the contribution rate of the intragroup gap and the intergroup gap to the total gap was investigated to better understand the current drug welfare induction level of Chinese patients with chronic diseases. Setting: The study was based in Gansu, Sichuan, Hebei, and Zhejiang provinces in China. Participants: Survey data was from patients with chronic diseases in 20 hospitals in four provinces. Primary and secondary outcome measures: Data was collected through a questionnaire designed by the research team after expert consultation. Using the variables represented by the index system to decompose the Theil index from the two dimensions of the region and urban and rural areas. SPSS 22.0 was used for reliability and validity analysis and Theil index calculation. Results: The overall level of drug welfare induction in Chinese patients with chronic diseases had a high degree of equalization. The overall Theil index was 0.0003, but there were still some differences among groups. Conclusions: To improve the drug welfare equalization induction level of patients with chronic diseases in China, the government should start from western rural areas, and policy should target the provinces that were in a disadvantaged position within the region to promote the equalization of drug welfare induction level for patients with chronic diseases in China.